The application of systems thinking in cattle production - Shane, Douglas (Kansas State University, 2016)
Applying systems methods to cattle production requires investigators to think about whole systems when addressing study objectives. The research conducted for this dissertation emphasized studying whole systems using different methods. We studied cattle production systems through mathematical simulation and new indirect monitoring technologies. While the methods used for the research in this dissertation may be very different, all utilized systems methods to address the study objectives. Firstly, we applied systems thinking methods and developed a dynamic, deterministic systems simulation of cow-calf production over a 10-year horizon. This model was used to investigate the effects the duration of postpartum anestrus (dPPA) has on reproductive performance. A large range of dPPA have been reported, so various primiparous cow and multiparous cow dPPA were simulated. We found that increasing the dPPA for primiparous and multiparous cows had a negative impact on herd performance and that the dPPA is an important factor in determining cow-calf performance success. We then used the cow-calf simulation to explore the effects of breeding nulliparous cows prior to the rest of the herd, known as providing Heifer Lead Time (tHL). We found that increasing tHL improved herd performance, especially with longer dPPA for primiparous cows. Secondly, real-time location systems (RTLS) were used to indirectly monitor cattle behavior. These systems have been used to determine the amount of time cattle spend at eating and drinking locations. We modeled the probability of cattle participating in eating and drinking behavior when determined to be at these locations by RTLS and found that significant differences exist between individual calves and period of the day. Finally, we explored associations between bovine respiratory disease (BRD) and animal-to-animal contacts as determined by RTLS in beef cattle. We found that the probability of BRD diagnosis was associated with the amount of time 4 days’ ago that a calf was in calf-contact with calves assumed to be shedding BRD pathogens.
Keywords: Cattle; Systems thinking; Bovine respiratory disease; Real-time location system; Cow-calf; Simulation